Problem-Based Learning Models: Their Effectiveness in Improving Creative Thinking Skills of Students with Different Academic Skills in Science Learning - Suciati, S.; Silvita, S.; Prasetyo, O.; Fauziah, M. D.; Santika, K. D.; Norawi, A. M.; Rahman, H. T. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study aims to 1) test the effectiveness of using simple and complex problem-based learning models in improving students' creative thinking skills and 2) test the effectiveness of simple and complex problem-based learning models in improving students' creative thinking skills based on different academic skills. This research was quasi-experimental with a pre-test-post-test non-equivalent control group design involving 96 students in grade VII taken by cluster random sampling including a control class with a simple problem-solving model (SPS), experimental class 1 using the Creative Problem Solving (CPS) learning model, and experimental class 2 using the IDEAL-Problem solving (IPS) learning model. The hypothesis test used the N-Gain Score and ANCOVA. The results reveal that the simple problem-based learning model, namely SPS, is less effective in improving students’ creative thinking skills. While complex problem-based learning models, namely CPS and IPS, are effective enough to improve students' creative thinking skills. Both simple and complex problem-based learning models can improve the creative thinking skills of students with different academic skills. Based on the results, it can be concluded that the most effective model for improving the creative thinking skills of students with different academic skills is the CPS learning model.